PENGARUH INVESTASI TEKNOLOGI INFORMASI DAN STRATEGI DIVERSIFIKASI TERHADAP NILAI PERUSAHAAN DENGAN PERTUMBUHAN PENJUALAN SEBAGAI VARIABEL MODERASI - Silvy Shapintia Farrakhan; Rosiyana Dewi (STMIK Widuri Jakarta, 2024)
The impact of the Covid-19 pandemic has had an impact on the main sectors of the Indonesian economy, especially on company value. A company can have high share movements on the stock exchange because of the company's value. Company value is a reflection of company performance, this can influence investor assessment. The focus of this research is on company financial reports published in 2018-2020, where there are 168 manufacturing companies registered on the IDX in 2018-2020 which were obtained by downloading the website. Using signal theory (signaling theory) with multiple linear regression analysis methods. From the research results, it was found that information technology investment has a positive influence on the value of a company, the higher the value of a company's technology investment, the higher the company value. The diversification strategy does not affect the company's value. Sales growth has a positive influence on company value. Sales growth moderates the influence of information technology investment on company value. Then sales growth does not moderate the effect of diversification strategy on company value.